Kebijakan Pendidikan Nasional Perspektif Pembiayaan Pendidikan - Juniaris Agung Wicaksono (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2021)
The fourth amendment of the 1945 Constitution article 31 states that: 1. Every citizen has the right to education. 2. Every citizen is obliged to attend basic education and the government is obliged to pay for it. 3. The government shall endeavor and organize a national education system that enhances faith and piety as well as noble character in the context of educating the nation's life which is regulated by law. 4. The state prioritizes the education budget at least 20% of the state revenue and expenditure budget as well as from the regional revenue and expenditure budget to meet the needs of national education administration. 5. The government advances science and technology by upholding religious values ​​and national unity for the advancement of civilization and the welfare of mankind. In accordance with the mandate of the VI amendment of the 1945 Constitution, Article 31 paragraph 4, which was later strengthened through Law Number 20 of 2003 concerning the National Education System, in particular the Fourth Part concerning the Allocation of Education Funds. Meanwhile, according to the National Education System Law Number 20 of 2003, Chapter XII article 46 paragraph 1 and Government Regulation Number 48 of 1008, education financing is a shared responsibility between the government, regional governments, and the community. The principles of managing these funds are: 1. Fairness. 2. Efficiency. 3. Transparency. 4. General